CODE MIXING USED BY TEENAGERS IN FACEBOOK - Ismarini Hutabarat; Lia Khalisa (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
This research dealst with Code Mixing Used by Teenagers in Facebook. The objective of the research was to find out the types of code mixing used by teenagers in their Facebook accounts status. The data analyzed were teenagers’ Facebook accounts status dated from 1st May until 31st July, 2019. The writer analyzed and interpreted the data based on Hoffman’s theory and qualitative design of research. The result of the study showed that there were three types of code mixing used by teenagers in their Facebook accounts status dated from 1st May until 31st July, 2019 based on Hoffman’s which were intra-sentential code mixing, intra-lexical code mixing and involving a change in pronunciation code mixing.